The accumulation of condensed tannins in local populations of sulla - Piluzza G.; Bullitta S.; Deroma M.; Odoardi M. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Aim of the study was the evaluation of the accumulation and content of condensed tannins (CT) during the life cycle of sulla (Hedysarum coronarium L.). The colorimetric method 'Butanol-HCl-Fe3plus' has been used and adapted to the species. Different phenological phases have been examined separately for both components leaves and stems. A comparison was initially made between the Southern Sardinian natural population 'Villanovafranca' and the commercial variety 'Grimaldi'; other four Sardinian natural populations of sulla were also analyzed. Leaves showed a considerable higher CT content than stems. Some natural populations showed higher CT concentration than 'Grimaldi'.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)